Efficacy and Safety of Corticosteroid Treatment in Patients With COVID-19: A Systematic Review and Meta-Analysis - Cheng, Wenwen; Li, Yufeng; Cui, Liyan; Chen, Ying; Shan, Sharui; Xiao, Duan; Chen, Xiaoyun; Chen, Zhuoming; Xu, Anding (Frontiers in Pharmacology, 2020)
Background: COVID-19 is a type of pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection that was identified in December 2019. Corticosteroid therapy was empirically used for clinical treatment in the early stage of the disease outbreak; however, data regarding its efficacy and safety are controversial. The aim of this study was to evaluate the efficacy and safety of corticosteroid therapy in patients with COVID-19. Methods: The PubMed, Cochrane Library, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, and China Science and Technology Journal (VIP) databases were searched for studies. Data on clinical improvement, mortality, virus clearance time, adverse events (AEs), utilization of mechanical ventilation, length of intensive care unit (ICU) hospitalization and hospital stay were extracted by two authors independently. Study quality was assessed by the Newcastle Ottawa Scale (cohort studies). The pooled data were meta-analyzed using a random effects model, and the quality of evidence was rated using the GRADE approach. Results: Eleven cohort studies (corticosteroid group vs control group), two retrospective cohort studies (without control group), and seven case studies were identified. A total of 2840 patients were included. Compared with the control treatments, corticosteroid therapy was associated with clinical recovery (RR=1.30, 95% CI [0.98, 1.72]) and a significantly shortened length of ICU hospitalization (RR=-6.50, 95% CI [-7.63, -5.37]), but it did not affect the mortality ((RR=1.59, 95% CI [0.69, 3.66], I2=93.5%), utilization of mechanical ventilation (RR=0.35, 95% CI [0.10, 1.18]), duration of symptoms (WMD=1.69, 95% CI [-0.24, 3.62]) or virus clearance time (RR=1.01, 95% CI [-0.91, 2.92], I2=57%) in COVID-19 patients. Treatment with corticosteroids in patients with COVID-19 may cause mild adverse outcomes. The quality of evidence was low or very low for all outcomes. Conclusion: The findings of our study indicate that corticosteroid therapy is not highly effective, but it appears to improve prognosis and promote clinical recovery in patients with severe COVID-19.